The Transformation of Dance and the Quality of Intergenerational Dance Performance - Mulyani, Sri; Hartono; Raharjo, Eko (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2026)
The role of traditional dancers as cultural agents significantly contributes to preserving the artistic identity of a region. However, in the face of rapid societal changes, the quality of performance artistry has undergone a significant transformation across generations. This article examines how the values of performance artistry have evolved, the challenges faced in preserving dance techniques and ethos, and the educational and cultural transmission strategies that can strengthen the quality of performance across generations. Using a qualitative approach through literature review and interviews with intergenerational artists, the study reveals that the transformation of performance artistry reflects a paradigm shift from mere technical inheritance to a more contextual actualization of cultural identity